Representasi Hero’s Journey Pada Tokoh Chihiro Dalam Anime Spirited Away Karya Miyazaki Hayao - Fajria Noviana (IZUMI, 2019)
(Title: Representation of Hero’s Journey on Main Character Chihiro in Hayao Miyazaki’s Spirited Away Anime) This paper is the result of a qualitative descriptive type of literature study. The purpose of this study was to reveal the heroic journey process of main character of Spirited Away anime named Chihiro, based on the Hero’s Journey theory proposed by Vogler. Data about Chihiro's heroic journey are obtained from anime with note taking techniques. The method used in the analysis is the method of content analysis based on the theory of Hero's Journey. From the results of the analysis, it can be seen that the main character Chihiro has undergone a total of the twelve stages of the hero’s journey. Chihiro's adventure has succeeded in changing her personality which was initially timid, spoiled, and whiny to be brave, independent, calm and confident, and full of compassion. Chihiro's heroic journey proves the true definition of a hero according to Vogler, while also proving that to win a fight does not always use physical strength. There are times when thinking intelligence and emotional intelligence are much more needed. In addition, this anime also features a lot of kamisama which was once believed by the Japanese. Miyazaki might want to remind again about the existence of Japanese gods by displaying them in this anime, either those actually found in Japanese mythology or Miyazaki's own creations. Thus, the story of Spirited Away which has a mythical structure as stated by Vogler becomes much more alive and interesting. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor